1999
DOI: 10.1080/00103629909370381
|View full text |Cite
|
Sign up to set email alerts
|

Differential genotypic tolerance response to manganese stress in triticale

Abstract: Manganese (Mn) tolerance response in two aluminum (Al)-tolerant triticale (× Triticosecale Wittmack) varieties was characterized by measurements of growth and dry matter production of seedlings in nutrient solution culture containing 100 mg L -1 Mn. Root weight index (RWI) and total weight index (TWI) based on relative plant growth were two indicators of differentiating genotypic Mn tolerance; these two indices were used to make a comparative assessment of the degree of Mn tolerance in a group of eight Austral… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2002
2002
2016
2016

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 11 publications
0
4
0
Order By: Relevance
“…2). Manganese toxicity is likely to affect root growth indirectly through the shoot injury caused by excess accumulation of Mn (Zhang et al, 1999 (Tang et al, 2003), is notable, and is in contrast to deficiencies of Zn Graham, 1995, 1996) and Mn (Khabaz-Saberi et al, 2002) that affect both root and shoot growth in wheat to a similar extent.…”
Section: Development Of a Screening Techniquementioning
confidence: 93%
“…2). Manganese toxicity is likely to affect root growth indirectly through the shoot injury caused by excess accumulation of Mn (Zhang et al, 1999 (Tang et al, 2003), is notable, and is in contrast to deficiencies of Zn Graham, 1995, 1996) and Mn (Khabaz-Saberi et al, 2002) that affect both root and shoot growth in wheat to a similar extent.…”
Section: Development Of a Screening Techniquementioning
confidence: 93%
“…Eight triticale genotypes which differed in Al tolerance were tested in nutrient solution for manganese tolerance (Zhang et al 1999b). A wide range of Mn tolerance was found but it did not correlate across genotypes with Al tolerance.…”
Section: Mineral Toxicitymentioning
confidence: 99%
“…Despite increase in aluminium and manganese in some genotypes over initial values, many genotypes managed to perform better. Zhang et al (1999) reported such genotypic tolerance of plants to Al and Mn toxicity.…”
Section: Resultsmentioning
confidence: 99%